New bryozoan species from the Pleistocene of the Wanganui Basin, North Island, New Zealand - Di Martino, Emanuela; Taylor, Paul D.; Gordon, Dennis P.; Liow, Lee Hsiang (European Journal of Taxonomy, 2017)
Three new fossil bryozoan species, a ctenostome and two cheilostomes, are described and figured from Pleistocene strata of the Wanganui Basin, New Zealand. Buskia waiinuensis sp. nov., a soft-body ctenostome preserved as a mould bioimmuration, is the first fossil record of the genus from New Zealand. Microporella rusti sp. nov., which is notable for the lack of ooecia in the large suite of colonies available, is one of the most common bryozoans in the Nukumaru Limestone and Nukumaru Brown Sand shellbeds, forming large encrusting sheet-like colonies, but is uncommon in younger beds. Rare, small-sized colonies of Parkermavella columnaris sp. nov. were found as fossil in two Quaternary beds, the Nukumaru Limestone and the Upper Kai-Iwi Shellbed, and also alive on rocks from the greater Cook Strait area.